Mini Review: Application of ionic liquids in acid hydrolysis of lignocellulosic material to obtain sugars (2021)
In recent decades, the application of ionic liquids (LI) as pretreatment of residual biomass (BM) prior to the hydrolysis reaction, has proven to be an efficient system to improve yields towards obtaining monosaccharides. A greater recovery of monosaccharides translates into a higher yield in the production of biofuels, which can make this industry profitable. In this context, this bibliographic review analyzes the physicochemical characteristics, synthesis methods, dissolution conditions with application of variables such as: LI: BM ratio, temperature and time. In addition, a comparative analysis of the results of traditional acid hydrolysis processes with respect to those obtained with the application of ionic liquids is carried out, increasing in most cases their reaction yields. Finally, some recovery and recycling techniques are mentioned, which allow to reduce the costs of the process, so that it is economically profitable.